2008
DOI: 10.1007/s10567-008-0030-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Family-based Program to Reduce Risk and Promote Resilience Among Families Affected by Maternal Depression: Theoretical Basis and Program Description

Abstract: Depression is a family matter. It not only diminishes the quality-of-life of the depressed person, but also strains the resources of the family unit and increases the children's risk of developing significant problems that start early and persist into adulthood. Although treatment of a parent's depression is critical, many families also need professional intervention to reduce children's risk. This article reviews the evidence on needs of these families and shows that the theoretical and clinical evidence exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 86 publications
4
97
0
3
Order By: Relevance
“…Although parents can have depressive symptoms that arise independently of the partner, these depressive symptoms have implications for other family members. Clinicians might therefore assist family members by providing information, as well as fostering communication and family problem-solving and coping skills, so that families can emerge stronger and more resourceful in meeting future challenges (Sanford et al 2003;Riley et al 2008). Furthermore, affirming family strengths and potential in the midst of difficulties might help family members to counter a sense of helplessness, and encourage them to take the initiative and face severe ordeals head on (Walsh 2002(Walsh , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Although parents can have depressive symptoms that arise independently of the partner, these depressive symptoms have implications for other family members. Clinicians might therefore assist family members by providing information, as well as fostering communication and family problem-solving and coping skills, so that families can emerge stronger and more resourceful in meeting future challenges (Sanford et al 2003;Riley et al 2008). Furthermore, affirming family strengths and potential in the midst of difficulties might help family members to counter a sense of helplessness, and encourage them to take the initiative and face severe ordeals head on (Walsh 2002(Walsh , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have shown that 23-29 % of mothers screen positive for clinically significant depressive symptoms (Bauer et al 2013;Olson et al 2005) and approximately 6 % meet diagnostic criteria for post-traumatic stress disorder (Chemtob et al 2013). Poor parental mental health negatively affects child wellbeing and family functioning (e.g., Barrett et al 1996;Burke 2003;Chemtob et al 2013;Downey and Coyne 1990;Garber et al 2009;Gershoff et al 2003;Hammen et al 2004;Malia 2007;Patterson and Cobb 1971;Patterson 1982;Riley et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While couple interventions have been reviewed recently (Beach & Whisman, 2012), family interventions taking the child's well-being into account got less attention. Based on an intervention to prevent negative outcomes and to improve coping skills in children of parents with mood disorder (Beardslee et al, 1992(Beardslee et al, , 1993(Beardslee et al, , 2003, recently a family focused intervention 'Keeping Families Strong' was developed (Riley et al, 2008;Valdez, Mills, Barrueco, Leis, & Riley, 2011). Both parents and their children were invited to group meetings as well as to individual family therapy sessions.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Both parents and their children were invited to group meetings as well as to individual family therapy sessions. The project using a combination of cognitive restructuring and solution-focused and narrative approaches shows good outcomes (Riley et al, 2008;Valdez et al, 2011). Cooklin (2006) described a similar prevention project, the 'Kidstime project', with outcomes such as children feeling less alone and parents feeling more respected as a parent.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%